Novel synergistic concrete additive
By adopting new synergistic concrete additives, combined with specific ingredients and preparation methods, the problem that existing concrete additives are difficult to improve corrosion resistance, wear resistance and crack resistance at the same time, achieving improvement in concrete performance and long-term durability extension.
Patent Information
- Application Number
- CN202411405108.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-11
- Filing Date
- 2024-10-10
- Publication Date
- 2025-03-04
AI Technical Summary
Existing concrete additives are difficult to improve the corrosion resistance, wear resistance and crack resistance of concrete at the same time. At the same time, there is a problem of incomplete hydration of cement in the early stage, which affects the long-term durability of concrete.
A new type of synergistic concrete additive is adopted, including water-absorbing resin, modified calcium oxide, cellulose, aluminum chloride hexahydrate, modified zirconia, zeolite, water reducing agent, expansion agent, coal gangue, chitosan, coupling agent, waste slag and anhydrous ethanol. Through specific mixing and preparation methods, concrete additives with synergistic effects are formed.
It significantly improves the corrosion resistance, wear resistance and crack resistance of concrete, enhances interface bonding and structural compactness, extends the service life of concrete, and reduces production costs.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete additives, and in particular to a novel synergistic concrete additive. Background Art
[0002] Concrete is one of the most commonly used building materials. Concrete is a composite material made by mixing cement, sand, gravel, and mineral admixtures evenly with water in appropriate proportions, and then evenly stirring, compacting, and curing to form it.
[0003] Concrete is composed of cementitious materials, coarse aggregate, fine aggregate, water and admixtures. Cementitious materials are mainly cement, supplemented by various admixtures, which play a decisive role in the strength and state of concrete. Coarse aggregate and fine aggregate are similar to muscles and bones in the human body, playing a filling and compacting role. Usually, in order to improve the strength of concrete, the first choice is to reduce the water-cement ratio. Reducing the water-cement ratio can reduce the defects of the concrete structure, reduce the amount of cement, and save costs, but it is easy to cause incomplete hydration of cement in the early stage, and slowly hydration in the later stage will cause damage to the hardened concrete structure.
[0004] After cement is mixed with water, a hydration reaction occurs. As the hydration reaction proceeds, the gels overlap each other, the free water content continues to decrease, and the slurry formed by cement and water gradually coagulates, hardens, and develops strength. Due to the molecular cohesion between cement particles, the cement slurry forms a flocculated structure, in which about 10-30% of the mixing water is wrapped in the flocculated structure and cannot flow freely. In order to reduce the formation of flocculated structure in cement slurry, synergists are usually added during the mixing process to improve the performance of cement. Summary of the invention
[0005] The invention provides a novel synergistic concrete additive.
[0006] The scheme of the present invention is: A novel synergistic concrete additive comprises the following raw materials in parts by weight: 2-4 parts of water-absorbing resin; 3-8 parts of modified calcium oxide; 6-9 parts of cellulose; 0.1-1 part of aluminum chloride hexahydrate; 10-20 parts of modified zirconium oxide; 10-18 parts of zeolite; 8-14 parts of water reducing agent; 6-9 parts of expansion agent; 4-10 parts of coal gangue; 3-4 parts of chitosan; Coupling agent 0.5-1 part; 5 to 9 parts of waste residue; 15-18 parts of anhydrous ethanol.
[0007] As a preferred technical solution, the following raw materials are included in parts by weight: 3 parts of water-absorbing resin; 6 parts of modified calcium oxide; 8 parts of cellulose; 0.5 parts of aluminum chloride hexahydrate; 16 parts of modified zirconium oxide; 14 parts of zeolite; 9 parts of water reducing agent; 7 parts of expansion agent; 8 parts of coal gangue; Chitosan 3 parts; 0.5 parts of coupling agent; 7 parts of waste residue; 16 parts of anhydrous ethanol.
[0008] As a preferred technical solution, the water reducer is a polycarboxylate water reducer mother liquor.
[0009] As a preferred technical solution, the expansion agent is a mixture of magnesium oxide and iron oxide soaked in an extractant, and the mass ratio of the iron oxide to magnesium oxide is 3:14.
[0010] As a preferred technical solution, the coupling agent is silane coupling agent KH-550.
[0011] As a preferred technical solution, the waste slag is ash coal powder and waste slag, and the mass ratio of the ash coal powder to the waste slag is 4-5:9-12.
[0012] The present invention also discloses a method for preparing a novel synergistic concrete additive, comprising the following steps: 1) Preparation of modified zirconium oxide, zirconium oxychloride and phosphoric acid solution with a mass concentration of 65% are added to a mixing container in a mass ratio of 1:1.2, stirred at 70-80°C for 4 hours, molybdenum oxide is added to the mixing container during the stirring process, and then the mixture in the beaker is filtered with a 150-mesh screen, and the filtered precipitate is placed in a dryer and dried at 200°C for 3 hours, and then the dried precipitate is mixed with magnesium carbonate, stirred for 10 minutes, and then fired at 1500-1600°C, the heating rate is controlled to be less than 20°C / h when the temperature is below 900°C, and the heating rate is controlled to be less than 25°C / h when the temperature is above 900°C, the heat preservation time is 6 hours, and after cooling, it is broken into particles with a particle size of less than 5 microns to obtain modified zirconium oxide; wherein, the mass ratio of the dried precipitate to the magnesium carbonate is 3.5:1; 2) 3 to 8 parts by weight of modified calcium oxide, 0.1 to 1 parts by weight of aluminum chloride hexahydrate, 10 to 18 parts by weight of zeolite, 4 to 10 parts by weight of coal gangue and 3 to 4 parts by weight of chitosan are mixed to obtain a mixture; 0.5 to 1 parts by weight of a coupling agent is dissolved in 15 to 18 parts by weight of anhydrous ethanol, and then the mixture and 2 to 4 parts by weight of a water-absorbing resin are added, stirred at 120 to 140° C., and then aged at room temperature for 12 to 25 hours, and 6 to 9 parts by weight of cellulose are added to obtain a mixture; 3) Take 10 to 20 parts by weight of the modified zirconium oxide in step 1), stir and mix with 8 to 14 parts by weight of a water reducer and 6 to 9 parts by weight of an expansion agent at a stirring speed of 30 to 40 r / min, add 5 to 9 parts by weight of waste slag during the stirring process, and stir for 20 to 30 minutes to obtain a synergist.
[0013] As a preferred technical solution, the mixture is mixed for 10 minutes and then fired at 1500°C.
[0014] Due to the adoption of the above technical scheme, a new type of synergistic concrete additive is provided, which includes the following steps: 1) preparation of modified zirconium oxide, adding zirconium oxychloride and a phosphoric acid solution with a mass concentration of 65% to a mixing container at a mass ratio of 1:1.2, stirring at 70-80°C for 4 hours, adding molybdenum oxide to the mixing container during the stirring process, then filtering the mixture in the beaker with a 150-mesh screen, placing the filtered precipitate in a dryer at 200°C for 3 hours, and then mixing the dried precipitate with magnesium carbonate and stirring for 10 minutes. Then, the zirconia is sintered at 1500-1600°C, the heating rate is controlled to be less than 20°C / h when the temperature is below 900°C, and the heating rate is controlled to be less than 25°C / h when the temperature is above 900°C, the heat preservation time is 6 hours, and the zirconia is crushed into particles with a particle size of less than 5 microns after cooling to obtain modified zirconium oxide; wherein the mass ratio of the dry precipitate to magnesium carbonate is 3.5:1; 2) 3-8 parts by weight of modified calcium oxide, 0.1-1 parts by weight of aluminum chloride hexahydrate, 10-18 parts by weight of zeolite, 4-10 parts by weight of coal gangue and 3-4 parts by weight of chitosan are mixed to obtain a mixture; 0 .5-1 weight parts of coupling agent are dissolved in 15-18 weight parts of anhydrous ethanol, and then the mixture and 2-4 weight parts of water-absorbing resin are added and stirred at 120-140°C, and then aged at room temperature for 12-25 hours, and 6-9 weight parts of cellulose are added to obtain a mixture; 3) 10-20 weight parts of modified zirconium oxide in step 1) are taken, and stirred with 8-14 weight parts of water reducer and 6-9 weight parts of expansion agent at a stirring speed of 30r / min-40r / min. 5-9 weight parts of waste residue are added during the stirring process, and stirred for 20-30 minutes to obtain a synergist.
[0015] Advantages of the present invention: After use, the corrosion resistance and wear resistance of concrete are improved, the interface adhesion with cement and other powders is improved, the density of the interface structure is increased, the formation of cracks is inhibited, and the durability of concrete is increased.
[0016] It helps to increase the cohesion of concrete mortar, reduce the rebound rate and shrinkage rate, improve the frost resistance of concrete, and is easy to use in harsh environments (plateaus and alpine areas); the preparation method provided by the invention has the advantages of simple operation, low equipment requirements, good construction performance and easy large-scale promotion and application.
[0017] The invention adopts common Portland cement commonly used in commercial concrete mixing stations, has a short concrete mixing time, low comprehensive cost, can realize large-scale production and application, and has broad application prospects.
[0018] The present invention greatly improves the compressive strength of concrete, effectively offsets the defect of decreased compressive strength caused by the addition of expansion agent, and makes the crack-resistant concrete have better compressive strength to better meet the needs of special projects. DETAILED DESCRIPTION
[0019] The invention provides a novel synergistic concrete additive.
[0020] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments. Example
[0021] 1) Preparation of modified zirconium oxide: add zirconium oxychloride and phosphoric acid solution with a mass concentration of 65% in a mass ratio of 1:1.2 to a mixing container, stir at 70-80°C for 4 hours, add molybdenum oxide to the mixing container during the stirring process, then filter the mixture in the beaker with a 150-mesh screen, place the filtered precipitate in a dryer and dry it at 200°C for 3 hours, then stir and mix the dried precipitate with magnesium carbonate, stir for 10 minutes, and then sinter at 1500°C, control the heating rate below 20°C / h when the temperature is below 900°C, and control the heating rate below 25°C / h when the temperature is above 900°C, and keep warm for 6 hours, and after cooling, crush it into particles with a particle size of less than 5 microns to obtain modified zirconium oxide; wherein the mass ratio of the dried precipitate to the magnesium carbonate is 3.5:1; 2) 3 parts by weight of modified calcium oxide, 0.1 parts by weight of aluminum chloride hexahydrate, 10 parts by weight of zeolite, 4 parts by weight of coal gangue and 3 parts by weight of chitosan are mixed to obtain a mixture; 0.5 parts by weight of a coupling agent is dissolved in 15 parts by weight of anhydrous ethanol, and then the mixture and 2 parts by weight of a water-absorbing resin are added and stirred at 120° C., and then aged at room temperature for 12 hours, and 6 parts by weight of cellulose are added to obtain a mixture; 3) Take 10 parts by weight of the modified zirconium oxide in step 1), stir and mix with 8 parts by weight of a water reducer and 6 parts by weight of an expansion agent at a stirring speed of 30 r / min, add 5 parts by weight of waste slag during the stirring process, and stir at 20 r / min to obtain a synergist.
[0022] The water reducer is a polycarboxylate water reducer mother solution.
[0023] The expansion agent is a mixture of magnesium oxide and iron oxide soaked in an extractant, and the mass ratio of iron oxide to magnesium oxide is 3:14. The extractant is propylene glycol, water and strontium nitrate, and the mass ratio is 1:70:0.6.
[0024] The coupling agent is silane coupling agent KH-550.
[0025] The waste residue is coal ash powder and waste slag, and the mass ratio of the coal ash powder to the waste slag is 4:9. Example
[0026] 1) Preparation of modified zirconium oxide: add zirconium oxychloride and phosphoric acid solution with a mass concentration of 65% in a mass ratio of 1:1.2 to a mixing container, stir at 80°C for 4 hours, add molybdenum oxide to the mixing container during the stirring process, then filter the mixture in the beaker with a 150-mesh screen, place the filtered precipitate in a dryer and dry it at 200°C for 3 hours, then stir and mix the dried precipitate with magnesium carbonate, stir for 10 minutes, and then sinter at 1600°C, control the heating rate below 20°C / h when the temperature is below 900°C, and control the heating rate below 25°C / h when the temperature is above 900°C, and keep warm for 6 hours. After cooling, crush it into particles with a particle size of less than 5 microns to obtain modified zirconium oxide; wherein the mass ratio of the dried precipitate to the magnesium carbonate is 3.5:1; 2) 8 parts by weight of modified calcium oxide, 1 part by weight of aluminum chloride hexahydrate, 18 parts by weight of zeolite, 10 parts by weight of coal gangue and 4 parts by weight of chitosan are mixed to obtain a mixture; 1 part by weight of a coupling agent is dissolved in 18 parts by weight of anhydrous ethanol, and then the mixture and 4 parts by weight of a water-absorbing resin are added, stirred at 140° C., and then aged at room temperature for 25 hours, and 9 parts by weight of cellulose are added to obtain a mixture; 3) Take 20 parts by weight of the modified zirconium oxide in step 1), stir and mix with 14 parts by weight of a water reducer and 9 parts by weight of an expansion agent at a stirring speed of 40 r / min, add 9 parts by weight of waste slag during the stirring process, and stir for 30 minutes to obtain a synergist.
[0027] The water reducer is a polycarboxylate water reducer mother solution.
[0028] The expansion agent is a mixture of magnesium oxide and iron oxide soaked in an extractant, and the mass ratio of iron oxide to magnesium oxide is 3:14. The extractant is propylene glycol, water and strontium nitrate, and the mass ratio is 1:70:0.6.
[0029] The coupling agent is silane coupling agent KH-550.
[0030] The waste residue is ash coal powder and waste slag, and the mass ratio of the ash coal powder to the waste slag is 5:12. Example
[0031] 1) Preparation of modified zirconium oxide: add zirconium oxychloride and phosphoric acid solution with a mass concentration of 65% in a mass ratio of 1:1.2 to a mixing container, stir at 75°C for 4 hours, add molybdenum oxide to the mixing container during the stirring process, then filter the mixture in the beaker with a 150-mesh screen, place the filtered precipitate in a dryer and dry it at 200°C for 3 hours, then stir and mix the dried precipitate with magnesium carbonate, stir for 10 minutes, and then sinter at 1500°C, control the heating rate below 20°C / h when the temperature is below 900°C, and control the heating rate below 25°C / h when the temperature is above 900°C, and keep warm for 6 hours. After cooling, crush it into particles with a particle size of less than 5 microns to obtain modified zirconium oxide; wherein the mass ratio of the dried precipitate to the magnesium carbonate is 3.5:1; 2) 6 parts by weight of modified calcium oxide, 0.5 parts by weight of aluminum chloride hexahydrate, 14 parts by weight of zeolite, 8 parts by weight of coal gangue and 3 parts by weight of chitosan are mixed to obtain a mixture; 0.5 parts by weight of a coupling agent is dissolved in 16 parts by weight of anhydrous ethanol, and then the mixture and 3 parts by weight of a water-absorbing resin are added, stirred at 120° C., and then aged at room temperature for 16 hours, and 8 parts by weight of cellulose are added to obtain a mixture; 3) Take 16 parts by weight of the modified zirconium oxide in step 1), stir and mix with 9 parts by weight of a water reducer and 7 parts by weight of an expansion agent at a stirring speed of 30 r / min, add 7 parts by weight of waste slag during the stirring process, and stir for 20 minutes to obtain a synergist.
[0032] The water reducer is a polycarboxylate water reducer mother solution.
[0033] The expansion agent is a mixture of magnesium oxide and iron oxide soaked in an extractant, and the mass ratio of the iron oxide to the magnesium oxide is 3:14. The mass ratio of the iron oxide to the magnesium oxide is 3:14. The extractant is propylene glycol, water and strontium nitrate, and the mass ratio is 1:70:0.6.
[0034] The coupling agent is silane coupling agent KH-550.
[0035] The waste residue is ash coal powder and waste slag, and the mass ratio of the ash coal powder to the waste slag is 4:11.
[0036] Comparative Example 1 is a synergist, which is different from Example 3 only in that modified zirconium oxide is not used.
[0037] Comparative Example 2 is a synergist, which is different from Example 3 only in that alumina hexahydrate is not used.
[0038] Comparative Example 3 is a synergist, which is different from Example 3 only in that the swelling agent is not soaked with the extractant.
[0039] Comparative Example 4 is a synergist, which is different from Example 3 only in that the water-absorbing resin is not used.
[0040] Performance testing and testing methods 1) applying the synergists obtained in Examples 1-3 and the synergists obtained in Comparative Examples 1-4 to concrete according to the following method to obtain corresponding concrete; The experiment used C30 concrete as the object, the cement used was ordinary Portland cement (Dingxin PO 42.5 cement), the sand used was medium sand, and the stone used was 5-25mm continuously graded crushed stone.
[0041] Concrete mix ratio (C30) of the synergist obtained in Examples 1-3 and Comparative Examples 1-4 kg / m 3 ; Cement 100, mineral powder 50, fly ash 30, sand 420, gravel 500, water 80, synergist 5; Comparative Example 5, i.e. the mix ratio of concrete without adding synergist (C30) kg / m 3 Cement 110, mineral powder 50, fly ash 30, sand 420, gravel 500, water 80; 2) The performance of concrete mixture shall be tested in accordance with GB / T50080 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures"; 3) Concrete strength is tested in accordance with GB / T50081 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete"; 4) The concrete rebound rate shall be tested in accordance with GB / T50081-2002 "Technical Code for Concrete and Its Products".
[0042] 5) The cracking index of each embodiment and comparative example was tested according to GB / T29417-2012 “Test method for drying shrinkage cracking performance of cement mortar and concrete”.
[0043] 6) The antifreeze properties of each embodiment and comparative example were tested in accordance with GB / T50082-2009 "Standard for Test Methods for Long-term and Durable Performance of Ordinary Concrete".
[0044] Group 28d compressive strength / Mpa Concrete rebound rate (%) 28d drying shrinkage 28d frost resistance F Cracking index Example 1 67.5 2.2 0.012 310 1% Example 2 65.2 3.3 0.003 328 1% Example 3 69.4 1.3 0.001 348 1% Comparative Example 1 51.6 7.8 0.06 228 2% Comparative Example 2 53.7 5.6 0.12 268 1% Comparative Example 3 54.6 8.4 0.09 214 1% Comparative Example 4 57.5 9.7 0.15 267 1% Comparative Example 5 49.8 12.6 0.25 186 2% The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A new type of synergistic concrete additive, characterized in that: The invention comprises the following raw materials in parts by weight: 2-4 parts of water-absorbing resin; 3-8 parts of modified calcium oxide; 6-9 parts of cellulose; 0.1-1 part of aluminum chloride hexahydrate; 10-20 parts of modified zirconium oxide; 10-18 parts of zeolite; 8-14 parts of water reducing agent; 6-9 parts of expansion agent; 4-10 parts of coal gangue; 3-4 parts of chitosan; Coupling agent 0.5-1 part; 5 to 9 parts of waste residue; 15-18 parts of anhydrous ethanol.
2. A novel synergistic concrete additive as claimed in claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 3 parts of water-absorbing resin; 6 parts of modified calcium oxide; 8 parts of cellulose; 0.5 parts of aluminum chloride hexahydrate; 16 parts of modified zirconium oxide; 14 parts of zeolite; 9 parts of water reducing agent; 7 parts of expansion agent; 8 parts of coal gangue; Chitosan 3 parts; 0.5 parts of coupling agent; 7 parts of waste residue; 16 parts of anhydrous ethanol.
3. A novel synergistic concrete additive as claimed in claim 1, characterized in that: The water reducer is a polycarboxylate water reducer mother solution.
4. A novel synergistic concrete additive as claimed in claim 1, characterized in that: The expansion agent is a mixture of magnesium oxide and iron oxide soaked in an extractant, and the mass ratio of the iron oxide to the magnesium oxide is 3:
14.
5. A novel synergistic concrete additive as claimed in claim 1, characterized in that: The coupling agent is silane coupling agent KH-550.
6. A novel synergistic concrete additive as claimed in claim 1, characterized in that: The waste residue is coal ash powder and waste slag, and the mass ratio of the coal ash powder to the waste slag is 4-5:9-12.
7. A method for preparing the novel synergistic concrete additive according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) Preparation of modified zirconium oxide, zirconium oxychloride and phosphoric acid solution with a mass concentration of 65% are added to a mixing container in a mass ratio of 1:1.2, stirred at 70-80°C for 4 hours, molybdenum oxide is added to the mixing container during the stirring process, and then the mixture in the beaker is filtered with a 150-mesh screen, and the filtered precipitate is placed in a dryer and dried at 200°C for 3 hours, and then the dried precipitate is mixed with magnesium carbonate, stirred for 10 minutes, and then fired at 1500-1600°C, the heating rate is controlled to be less than 20°C / h when the temperature is below 900°C, and the heating rate is controlled to be less than 25°C / h when the temperature is above 900°C, the heat preservation time is 6 hours, and after cooling, it is broken into particles with a particle size of less than 5 microns to obtain modified zirconium oxide; wherein, the mass ratio of the dried precipitate to the magnesium carbonate is 3.5:1; 2) 3 to 8 parts by weight of modified calcium oxide, 0.1 to 1 parts by weight of aluminum chloride hexahydrate, 10 to 18 parts by weight of zeolite, 4 to 10 parts by weight of coal gangue and 3 to 4 parts by weight of chitosan are mixed to obtain a mixture; 0.5 to 1 parts by weight of a coupling agent is dissolved in 15 to 18 parts by weight of anhydrous ethanol, and then the mixture and 2 to 4 parts by weight of a water-absorbing resin are added, stirred at 120 to 140° C., and then aged at room temperature for 12 to 25 hours, and 6 to 9 parts by weight of cellulose are added to obtain a mixture; 3) Take 10 to 20 parts by weight of the modified zirconium oxide in step 1), stir and mix with 8 to 14 parts by weight of a water reducer and 6 to 9 parts by weight of an expansion agent at a stirring speed of 30 to 40 r / min, add 5 to 9 parts by weight of waste slag during the stirring process, and stir for 20 to 30 minutes to obtain a synergist.
8. A novel synergistic concrete additive as claimed in claim 1, characterized in that: After mixing for 10 minutes, the mixture is fired at 1500°C.